DFT studies of structural–electronic correlation for the HAT6 discotic liquid crystal columnar stacking - Mahmood, Mohamad Syafie; Said, Suhana Mohd; Chatterjee, Abhijit; Sabri, Mohd Faizul Mohd; Mainal, Azizah; Daud, Mohammad Noh; Sairi, Nor Asrina (IOP Publishing, 2018)
Discotic liquid crystals (DLC) have shown much promise for 1-D charge transport and relatively high charge mobility due to π-π conjugation of their cores. However, development of DLCs in molecular electronics are hindered by a lack of systematic study of DLCs' molecular conformation and its effect on the electronic properties. This study takes a model DLC molecule, 2, 3, 6, 7, 10, 11-hexahexyloxytriphenylene (HAT6) and calculates the electronic properties as a function of the columnar structural parameters (co-facial distance, twist and lateral slide) from (density functional theory) DFT calculations. The relationship between the structural parameter to band gap, electronic density of state (DOS) and partial DOS, charge population analysis, and electronic density mapping is discussed.